Chemical structure and anti-inflammatory activity of a branched polysaccharide isolated from Phellinus baumii. (15th September 2021) - Sun, Yuqing; Huo, Jinxi; Zhong, Shi; Zhu, Jianxun; Li, Yougui; Li, Xiaojun
Abstract: Phellinus baumii is used to treat inflammatory bowel disease (IBD) and gastroenteritis. In this study, a 46 kDa heteropolysaccharide SHPS-1 was isolated from fruiting bodies of P. baumii . SHPS-1 consisted of arabinose, mannose, glucose, and galactose at a molar ratio of 2.2:15.7:49.3:32.8. SHPS-1 had a backbone containing 1, 3-linked β-D-Glc p and 1, 6-linked α-D-Gal p residues, and Ara f, Man p and Gal p units were attached as oligosaccharidic side chains to the backbone at C-6 of some glucopyranoses. SHPS-1 decreased phosphorylation level of STAT-1 and expression levels of STAT-1 targeted genes such as iNOS and TNF-α in lipopolysaccharide-stimulated macrophage RAW 264.7 cells. Furthermore, SHPS-1 promoted the expression of IL-10 and macrophage mannose receptor CD 206, markers of tissue repairing macrophages. SHPS-1 alleviated ulcerative colitis in mice by decreasing pro-inflammatory genes and increasing anti-inflammatory and tissue repairing genes. Collectively, SHPS-1 polysaccharide from P. baumii had anti-inflammatory activity and can potentially treat IBD. Highlights: Polysaccharide SHPS-1 was isolated from fruiting bodies of mushroom Phellinus baumii . SHPS-1 contains 1, 3-linked β-D-Glc p and 1, 6-linked α-D-Gal p units in backbone. Araf, Man p and Gal p units are attached as side chains to the backbone at C-6 of glucopyranoses. SHPS-1 is anti-inflammatory and can potentially treat inflammatory bowel disease. SHPS-1 decreased STAT-1 phosphorylation and stimulated macrophage mannose receptor.